INFLAMMATORY LINEAR VERRUCOUS EPIDERMAL NAEVUS (ILVEN) - M. M. Tlish; N. L. Sycheva; P. S. Osmolovskaya; F. A. Psavok (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Etiopathogenic factors of ILVEN occurrence are considered in the article. There are clinical and morphological criteria to verify this pathology, such as: beginning of the disease at an early age, women predominance among the cases, the presence of linear rash resembling psoriasis, skin itching, frequent rash localization in the left lower limb, resistance to treatment, and histological features, which combine features of verrucous epidermal nevus with eczematization phenomena in the epidermis or psoriaziformnymi changes. The article describes clinical case of unilateral linear warty rash for pregnant women, which illustrated the relationship of cutaneous manifestations pathological process and its further course in connection with pregnancy.